Interactive E-Module Based on Differentiated PBL to Improve Critical Thinking Skills in Fractions in Grade IV Elementary School - Dwi Pradarta; I Nyoman Laba Jayanta; Komang Sujendra Diputra (Jurnal Edutech Undiksha, 2025)
Elementary school students’ critical thinking skills in fraction topics remain low, primarily due to the limited availability of interactive learning media that can accommodate diverse learning styles. This study aims to develop and examine the effectiveness of a differentiated, problem-based learning (PBL) based interactive e-module in improving students’ critical thinking skills. The research employed a Research and Development (R&D) method using the ADDIE development model, which includes the stages of analysis, design, development, implementation, and evaluation. The research design applied was a one-group pre-test–post-test, with Grade IV students as the subjects. Data were collected through questionnaires and descriptive tests using expert validation instruments, response questionnaires, and critical thinking skills tests, then analyzed qualitatively and quantitatively, including a paired t-test. The results indicated that the developed media had very high validity (average scores of 4.8 from subject matter experts and 4.6 from media experts), high practicality (93.55% from teachers and 98.5% from students), and significant effectiveness (significance value 0.000 < 0.05). This e-module was designed to meet diverse learning needs through a differentiated approach, offering interactivity and fostering active student engagement. In conclusion, the differentiated PBL-based interactive e-module proved to be valid, practical, and effective in enhancing conceptual understanding and critical thinking skills. The implication is that this media can be integrated into mathematics learning as an innovative solution to optimize learning outcomes and student engagement across various educational contexts.